DAMPAK KEBERADAAN HUTAN TANAMAN INDUSTRI PT. WANA SUBUR LESTARI TERHADAP KESEJAHTERAAN MASYARAKAT DESA SUNGAI RADAK II KECAMATAN TERENTANG KABUPATEN KUBU RAYA - Radian, Syafaruddin, Abdul Hamid A. Yusra, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
This study aimed to determine the impact of Industrial Plantation Forest of PT. Wana Subur Lestari on peopleâ€™s welfare in the village of River Radak II. These impacts include increased income, job opportunities, public facilities, public health, social agencies, employment and public welfare. The results of this study are expected to be useful for the implementation of rural development, the improvement of peopleâ€™s welfare, in the research area in particular and in Kubu Raya regency in general. This study used secondary data taken from relevant agencies and primary data in from of opinion taken from rural community of Sungai Radak II who have been affected by the presence of industrial plantation forest. To analyze the data of this research, SPSS 18.00 was used. The result of this research showed that the presense of Industrial Plantation Forest provides positive impact on the increased income, business opportunities, employment and public welfare. Furthermore, it does not have negative impact on public health and social agencies in the village of Sungai Radak II. The statistical result of income showed thatÂ tÂ value was -4,905 with sig (2 tailed) indicating that presence of Industrial Plantation Forest of PT. Wana Subur Lestari provides significant impact on peopleâ€™s income. The average level of well being was â€œaverage (40% - 75% of income for the use of food consumption per year)â€ Â Key Words: Impact, Welfare,Village ofÂ Sungai Radak II